Amorphization of MoS2 Cocatalysts on CdS Nanorods via Facet-Selective Deposition for Photocatalytic Hydrogen Evolution - Zhang, Fengying; Hong, Yujie; Yao, Zehan; Li, Yi; Zheng, Shenshen; Yu, Shan; Yartsev, Arkady ; 0000-0003-4941-4848; Zheng, Kaibo; Pullerits, Tonu; Zhou, Ying (ACS Applied Nano Materials, 2025)
The construction of heterojunctions between catalysts and cocatalysts is a widely recognized strategy to enhance catalytic activity. The precise placement of cocatalysts is widely understood to optimize charge transfer pathways and catalytic active sites. In this study, we demonstrate that site-selective decoration on an anisotropic catalyst, achieved by modulating solvent polarity and precursor reactivity during hydrothermal synthesis, can precisely control the structural properties of the cocatalysts. Using a benchmark CdS-MoS2 heterojunction system, where MoS2 cocatalysts are selectively grown on the tips and sides of CdS nanorods, we reveal that tip-decorated MoS2 adopts a quasi-amorphous structure with abundant defect states. This structural distortion stems from the greater lattice mismatch between MoS2 and the (002) facets of the CdS nanorod tips compared to their side (101) facets. These defects can serve as additional active sites, enhancing surface activation. Ultrafast photophysical studies further confirm that charge transfer between quasi-amorphous MoS2 and CdS (CdS/MoS2) is as efficient as that in its crystalline side-decorated counterparts (CdS@MoS2). Consequently, CdS/MoS2 achieves a photocatalytic efficiency of 6.7 mmol g-1 h-1, a significant 2-fold improvement over 2.9 mmol g-1 h-1 observed for CdS@MoS2. This work introduces an approach to optimizing photocatalytic performance through controlled cocatalyst growth in hybrid catalyst systems.
Keywords: carrier dynamics; cocatalysts; growth modulation; hydrogen evolution; quasi-amorphous structure